Step-by-step explanation and answer:
Setting up a system of equations would be the easiest method for this question. The first number will be x. The second number will be y. According to the question:
x+1=y
2x-4=5y
Since the first equation is already solved for y, you can plug the whole first equation in for y in the second equation, then solve for x.
2x-4=5(x+1) Distribute the 5
2x-4=5x+5 Subtract 5x from 2x
-3x-4=5 Subtract -4 from 5 (add 4 to 5)
-3x=9 Divide to get the x by itself
-3=x
Now that you have x solved for, you can plug it into the first equation (or second, if you prefer) to solve for y.
x+1=y
-3+1=y
-2=y